1992
DOI: 10.1002/star.19920440307
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of Hydroxypropyl Potato Starch Granules Depending on Their Molar Substitution

Abstract: The structural changes of potato starch granules, caused by hydroxy‐propylation, were studied using light microscopy. The starch samples used consisted of a native potato starch, hydroxypropyl potato starches with varying molar substitution (M. S.) and a hydroxypropyl and cross‐linked potato starch. The structural characteristics of the samples were evaluated by comparing the colour intensities of thin sections of samples stained with iodine and Schiff's reagent. The manner of loss of birefringence of samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 15 publications
8
34
0
Order By: Relevance
“…The affected granules appeared as folded structures with their outer side drawn inwards, giving the appearance of a doughnut. The results agreed with those reported by (Kim et al 1992), who suggested that most of the structural changes take place at the relatively less organized central region of the starch granule, i.e., where. the hydroxyproply groups are most densely deposited.…”
Section: Granule Morphologysupporting
confidence: 92%
“…The affected granules appeared as folded structures with their outer side drawn inwards, giving the appearance of a doughnut. The results agreed with those reported by (Kim et al 1992), who suggested that most of the structural changes take place at the relatively less organized central region of the starch granule, i.e., where. the hydroxyproply groups are most densely deposited.…”
Section: Granule Morphologysupporting
confidence: 92%
“…However traces of degradation were observed on some starch granules after modification. Changes in appearance of starch granules after hydroxypropylation have been reported for potato starches (Kim et al, 1992) and cassava starch (Jyothi et al, 2007). Also, no change in surface and shape characteristics of the granules was reported for canna starches in a previous work (Chuenkamol et al 2007).…”
Section: Scanning Electron Microscopy (Sem) and Granule Morphologymentioning
confidence: 93%
“…Differences were considered to be significant when p < 0.05. a short period of time (MILLER, 1988). Extrusion promotes a high physical modification in granular structure, increasing water absorption and retention (LIMBERGER et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Modified starches have been proposed as fat substitutes in several foods, such as cheese (SIPAHIOGLU; ALVAREZ; SOLANO-LOPEZ, 1999), beef patties (KHALIL, 2000) and ice-cream (JIMENEZ-FLORES; KLIPFEL; TOBIAS, 1993;AIME et al, 2001). The rheological properties of starch may be improved or adapted to technological needs through physical (extrusion) or chemical (phosphorylation) modification (BRANEN;DAVIDSON;SALMINEN, 1990;KIM;HERMANSON;ERIKSSON, 1992;ELIASSON;GUDMUNDSSON, 1996;SIVAK;PREISS, 1998;ALVES;GROSSMANN;SILVA, 1999;STAHL et al, 2007). Starch phosphates prepared through chemical methods produce clear pastes of high consistency, good freeze/thaw stability, lower gelatinization temperatures and high swelling power and solubility (SIVAK;PREISS, 1998;SITOHY et al, 2000a;STAHL et al, 2007).…”
Section: Introductionmentioning
confidence: 99%